(3SDGd aj GdJaSjQ (B:s (3eMGhdI aj GdHMK Yf efgL (B/s (3GdLRA GdKGfj s - (3GdRHjOj, SYjO LGSes ((3YeGf (B- (3GdCQOf (B: s (3OGQ cfhR GdeYQaI ddfTQ hGdJhRjY ,s, 2017)
(3gPG GdcJGH ddcGJH SYjO GdRHjOj, jJfGhd gPG GdcJGH fXQGJ aj BjGJ bQBfjI cQjeI Ydi ZjQ eG jhLO aj cJH eYGfj GdbQBf GdcQje, hcJH GdJaSjQ GdeYQhaI bOjeG hMOjKG, hjMGhd Cf jQSe eYGde efgL jJecf ajg WdHI GdYde ef GJNGPg WQjbG aj HMhKge hOQGSGJge hMdbGJ fbGTge, heYdeG Edi eQGO Gddg JYGdi, Ch ebGQHI dg(B.s
(3GdLRA GdChd ZjQ ehLhO s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
(3jJhGaQ HGdecJHI (B: (3eLdO (B2.s
Keywords: (3GdbQBfs -- (3JaSjQs -- (3efGgLs; (3GdbQBf s -- (3efGgL s